Ingesting isomaltulose versus fructose-maltodextrin during prolonged moderate-heavy exercise increases fat oxidation but impairs gastrointestinal comfort and cycling performance - Oosthuyse, T.; Carstens, M.; Millen, A. M. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Certain commercial carbohydrate replacement products include slowly absorbed carbohydrates such as isomaltulose. Few studies have investigated the metabolic effects of ingesting isomaltulose during exercise and none have evaluated exercise performance and gastrointestinal comfort. Nine male cyclists participated postprandially during three trials of 2-h steady-state (S-S) exercise (60%Wmax) followed by a 16 km time trial (TT) while ingesting 63 g·h-1 of either, 0.8:1 fructose: maltodextrin (F:M) or isomaltulose (ISO) or placebo-flavored water (PL). Data were analyzed by magnitude-based inferences. During S-S exercise, ISO and PL similarly increased plasma nonesterified fatty acid (NEFA) concentration (mean change ISO versus F:M: 0.18, 90%CI ±0.21 mmol·L-1, 88% likelihood) and fat oxidation (10, 90%CI ±9 g, 89% likelihood) while decreasing carbohydrate oxidation (-36, 90%CI ±30.2 g, 91% likelihood) compared with F:M, despite equal elevations in blood glucose concentration with ISO and F:M. Rating of stomach cramps and bloating increased progressively with ISO (rating: 0-90 min S-S, weak; 120 min S-S, moderate; TT, strong) compared with F:M and PL (0-120 min S-S and TT, very weak). TT performance was substantially slower with ISO (mean change: 1.5, 90%CI ±1.4 min, 94% likely harmful) compared with F:M. The metabolic response of ISO ingestion during moderate exercise to increase NEFA availability and fat oxidation despite elevating blood glucose concentration is anomalous for a carbohydrate supplement. However, ingesting isomaltulose at a continuous high frequency to meet the recommended carbohydrate replacement dose, results in severe gastrointestinal symptoms during prolonged or high intensity exercise and negatively affects exercise performance compared with fructose-maltodextrin supplementation.